Detection of ESR1 Mutations in Single Circulating Tumor Cells on Estrogen Deprivation Therapy but Not in Primary Tumors from Metastatic Luminal Breast Cancer Patients - Franken, André; Honisch, Ellen; Reinhardt, Florian; Meier-Stiegen, Franziska; Yang, Liwen; Jaschinski, Sandra; Esposito, Irene; Alberter, Barbara; Polzer, Bernhard; Hübner, Hanna; Fasching, Peter; Pancholi, Sunil; et al. (Journal of Molecular Diagnostics, 2020)
Mutations in the ligand-binding domain (LBD) of the ESR1 gene result in resistance to estrogen deprivation therapy (EDT) in breast cancer. Their detection might enable optimization of therapy strategies. However, the predictive utility of the primary tumor (PT) is limited, and obtaining serial biopsies of metastatic lesions is challenging. To underline their application as a liquid biopsy, single circulating tumor cells (CTCs) were analyzed with a next-generation sequencing approach for the ESR1 coding region. CTCs from 46 metastatic luminal breast cancer patients were enriched using CellSearch system and isolated by micromanipulation. Their genomic DNA was amplified and the ESR1 gene was sequenced. Furthermore, tissue samples from corresponding PTs and/or metastatic lesions were investigated. ESR1 mutations were detected in 12 patients—exclusively in patients treated with EDT (P = 0.048). In seven cases mutations were located in the hotspot regions in the LBD. Six novel mutations were identified. ESR1 mutations were absent in PT tissue samples and were detected only in metastases obtained after CTC characterization. Single-cell CTC analysis for ESR1 mutations could be of clinical value to identify patients who progress under EDT and therefore benefit from an early switch to an alternative endocrine therapy or other treatment regimens. Furthermore, our data indicate that mutations outside the LBD's hotspot regions might also contribute to resistance to EDT.
CRIS-Team Scopus Importer:2019-12-20